Experiences with economic reform : a review of Bangladesh's development, 1995 - Experience with economic reform; Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press Ltd., 1995)
Contributed articles.
Includes bibliographical references.
Keywords: Bangladesh -- Economic policy; Bangladesh -- Economic conditions